Analisis Penyebab Pembetulan Spt Ppn Sebagai Pemenuhan Kewajiban Pelaporan Spt Ppn. (Studi Kasus Pt. Pgp) - Yuliandi, Yuliandi (Institut Bisnis dan Informatika Kesatuan, 2019)
Taxes are the backbone of development, due to its contribution of more than 75% of total state revenues. Value added tax (VAT) in our country adheres to a self assessment system, which means that taxpayers calculate, deposit and report their own tax obligations, so the possibility of errors in reporting VAT Reporting (SPT) is still common issues. If an error occurs after the VAT SPT has been reported, taxpayers are obliged to submit correction of the VAT SPT that has been reported. This study uses a quantitative descriptive method with a case study approach. The obtained and collected data were then processed to make known what causes correction of VAT SPT at PT.PGP during 2016-2017. The results showed that the cause of the VAT SPT correction owing to errors when issuing invoice. Such errors arised due to request from the customers, editorial differences in the invoice, and the date of the invoice, and there were also issues in time compliance.